Nilai-nilai civic culture dalam tradisi turun tanah - Wahyuda Wahyuda; Zaky Farid Luthfi; Isnarmi Moeis; Tetti Eka Purnama (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to describe the implementation of the Turun Tanah Tradition as a medium for developing civic cultural character and to identify the civic culture values contained within it. This research employed a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation using purposive sampling techniques. The informants consisted of traditional leaders, families carrying out the tradition, and community members involved in the activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the Turun Tanah Tradition is still carried out through several stages, namely family deliberation, preparation of equipment and necessities, communal cooking activities, as well as prayers and ritual ceremonies. This tradition contains civic culture values such as kinship, religiosity, social values, and economic values that play a role in shaping community character. Through this tradition, social interaction, the spirit of mutual cooperation, and a sense of togetherness are created, which strengthen the cultural identity of the community. However, the implementation of the Turun Tanah Tradition has undergone changes due to the influence of modernization and demands for efficiency, causing its implementation to become simpler and limited to the family sphere, which has resulted in decreased community participation on a broader scale. Therefore, preservation efforts are needed through increasing public awareness, involving younger generations in every stage of the tradition, and adapting the tradition to contemporary developments without eliminating its core values.